PREVALENCE OF ANEMIA: AUDIT OF A LARGE SINGLE CENTER HEMODIALYSIS PATIENT POPULATION - Nabiha Rizvi; Najeeb Ullah Malik; Sohail Kamran; Rehan Ashraf; Saima Gill; Sajeela Ijaz (Pakistan Journal of Kidney Diseases, 2021)
Introduction: Chronic kidney disease (CKD) is increasingly being recognized as a global public health problem. Anemia is the most common manifestation and challenging problem in our dialysis population leading to multiple complications and poor quality of life. Methods: It was a cross sectional study done on 141 hemodialysis patients being dialyzed twice per week at Hijaz Hospital Lahore. The target hemoglobin level was according to KDIGO 2012 guidelines, 10-11.5g/dl. Results: Out of 141 patients, 69(48.9%) patients were found to be anemic. Among them 22(33.3%) were females and 47(66.6%) were male patients. Conclusion: In this study almost half of the patients were suffering from anemia suggesting that we still need to improve our practices regarding this aspect in our dialysis patients.